A methodology for the sport industry to capture public perceptions and responses in the time of COVID-19 - Wang, Y.-Y.; Wang, T.; Yoon, K. (Journal of Emerging Technologies in Accounting, 2021)
The COVID-19 pandemic has had an unprecedented impact on the sports industry, affecting from professional sports activities to the 2020 Summer Olympics. It has wreaked havoc on the sports calendar, causing a number of events to be canceled or postponed. This study proposes a methodology by which the sports industry can assess public perceptions and responses in social media to gain important insights that can be used to craft effective crisis management strategies. Using machine learning approaches in order to extract hidden patterns in tweets could assist practitioners in creating and implementing crisis communication strategies for mitigating the impact of COVID-19.